PA 12-6-0530 Burns among under-fives in an urban slum in kampala, uganda: prevalence and risk factors. (November 2018) - Tusiime, Marcia; Mutto, Milton; Musoke, David
Abstract : Background: Globally, burn deaths are disproportionately higher among children below five years compared to other age groups. Although rarely fatal, most burns among this age group occur within the home environment specifically in the kitchen. Objective: This study assessed the prevalence and factors associated with burns occurring at household level among under-fives living in Kisenyi, an urban slum in Kampala, Uganda. Methods: A cross sectional study using both quantitative and qualitative methods was used. After stratification, simple random sampling was used to obtain a sample size of 426 children below 5 years. Purposive sampling was used to identify 6 key informants. Questionnaires, observation checklists and interview guides were used as data collection tools. A modified Poisson regression model was used to determine the correlates of burns. Findings: Prevalence of burns was 32% and children aged 24 to 35 months (39%) were most affected. More boys (52.4%) had suffered burns. Children with single parents (adj PR=1.56 95% CI: 1.07–2.29) were more likely to suffer burns while those born to foreigners had a lower risk (adj.PR=0.5; 95% CI: 0.28–0.91). Households within the middle and richest wealth quintile (adj.PR=1.72; 95% CI: 1.02–2.89 and adj.PR=1.77; 95% CI: 1.02 to 3.05) had children with increased risk of burns. Through observation, households with flammables properly stored had a reduced a child's burn injury likelihood (adj.PR=0.61; 95% CI: 0.44–0.83) when compared to their counterparts. Conclusion: Prevalence of burns was high. Socio economic factors were shown to be more associated with childhood burns. Injury prevention efforts for similar urban slum settings should focus on community education and enforcement of home safety standards. Policy implication: In light of the high burn prevalence in Kisenyi slum, urban authorities should invest more in injury research so as to identify risk factors for burns. This scientific evidence once generated can be used for planning burn prevention programs.